Genetic variability, heritability, association and divergence studies in safflower (Carthamus tinctorius L.) genotypes: GENETIC VARIABILITY, HERITABILITY, ASSOCIATION AND DIVERGENCE STUDIES IN SAFFLOWER - S NEELIMA; K PRABHAKAR; K V RAMANAMMA (Journal of Oilseeds Research, 2021)
Genetic variability, heritability, genetic advance, divergence, association and path analysisstudieswere carried out in 13 safflower genotypes for nine yield and its contributing traits. Results of ANOVA showed highly significant mean sum of squares for all the traits indicating presence of high variability in the experimental material. Wide range of variation was noticed in seed yield followed by plant height, number of capitula/plant and number of seeds/capitulum. High phenotypic and genotypic coefficient of variation were recorded for number of seeds/capsule, 100 seed weight and seed yield. Low heritability coupled with high genetic advance as percent of mean was exhibited for seed yield indicated that yield is governed by additive gene effects and is highly influenced by environment. Hull content recorded strong correlation with seed yield followed by volume weight and 100 seed weight and in turn these traits were also strongly inter-correlated. Volume weight had high direct effect on seed yield and its indirect effect via hull content and 100 seed weight was also of high magnitude. In the experimental material, genetic divergence was mainly contributed by oil content, days to 50% flowering and number of seeds/capitulum.